2021
DOI: 10.1037/rev0000252
|View full text |Cite
|
Sign up to set email alerts
|

Information gaps for risk and ambiguity.

Abstract: We apply a model of preferences for information to the domain of decision making under risk and ambiguity. An uncertain prospect exposes an individual to an information gap. Gambling makes the missing information more important, attracting more attention to the information gap. To the extent that the uncertainty (or other circumstances) makes the information gap unpleasant to think about, an individual tends to be averse to risk and ambiguity. Yet when an information gap happens to be pleasant, an individual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 109 publications
(142 reference statements)
0
16
0
Order By: Relevance
“…Such stable individual differences can be regarded as the consequence of the repetitive self-boosting processes in the proposed framework. Although there has been growing body of theoretical work on curiosity and interest (Dubey & Griffiths, 2020; Golman et al, 2021; Gruber & Ranganath, 2019; Kashdan et al, 2018; Sharot & Sunstein, 2020; Thoman et al, 2017), the proposed framework is the only account that integrates the three distinct research traditions from a coherent theoretical perspective. The proposed framework also clarifies commonalities as well as differences between behavioral regulation based on interest and on extrinsic rewards: While the framework maintained the common reward-learning properties between them, the framework also revealed several distinct features that represent interest-based engagement (i.e., self-boosting effect, selectivity, vulnerability, and under-appreciation).…”
Section: Discussionmentioning
confidence: 99%
“…Such stable individual differences can be regarded as the consequence of the repetitive self-boosting processes in the proposed framework. Although there has been growing body of theoretical work on curiosity and interest (Dubey & Griffiths, 2020; Golman et al, 2021; Gruber & Ranganath, 2019; Kashdan et al, 2018; Sharot & Sunstein, 2020; Thoman et al, 2017), the proposed framework is the only account that integrates the three distinct research traditions from a coherent theoretical perspective. The proposed framework also clarifies commonalities as well as differences between behavioral regulation based on interest and on extrinsic rewards: While the framework maintained the common reward-learning properties between them, the framework also revealed several distinct features that represent interest-based engagement (i.e., self-boosting effect, selectivity, vulnerability, and under-appreciation).…”
Section: Discussionmentioning
confidence: 99%
“…One interesting noneconomic motive that may drive backers’ decision is uncertainty seeking. Backers may enjoy betting on the success of Kickstarter projects either because they derive utility from resolving the uncertainty—an information gap that is pleasant to think about (Golman, Loewenstein, and Gurney 2015)—or because uncertainty about obtaining a positive outcome (i.e., receiving a reward offered by a project) induces excitement (Shen, Fishbach, and Hsee 2015). This may lead backers to more eagerly support a project before it reaches its funding goal—that is, when its campaign outcome is still uncertain.…”
Section: Robustness and Alternative Explanationsmentioning
confidence: 99%
“…A growing literature has begun to characterize how people make information-seeking decisions. For example, it has been shown that people want information more when it will likely reveal good rather than bad news (Charpentier, Bromberg-Martin, & Sharot, 2018;Karlsson, Loewenstein, & Seppi, 2009;van Lieshout, de Lange, & Cools, 2020;van Lieshout, Traast, de Lange, & Cools, 2021), when uncertainty is high (Bromberg-Martin & Monosov, 2020;Chater & Loewenstein, 2016;Cogliati Dezza, Yu, Cleeremans, & Alexander, 2017;Crupi, Nelson, Meder, Cevolani, & Tentori, 2018;Friston, 2010;Golman, Gurney, & Loewenstein, 2020;Golman & Loewenstein, 2018;Gottlieb, Oudeyer, Lopes, & Baranes, 2013;Kidd & Hayden, 2015;Kobayashi, Ravaioli, Baranes, Woodford, & Gottlieb, 2019;Oudeyer, Lopes, Kidd, & Gottlieb, 2016;Schulz et al, 2019;Schwartenbeck et al, 2019;, and when the instrumental utility of information (e.g., the ability of information to guide future actions towards high rewards) is great (Cogliati Dezza, Cleeremans, & Alexander, 2022;Kobayashi & Hsu, 2019;Stigler, 1961;Wilson, Geana, White, Ludvig, & Cohen, 2014). Presumably this is because people are motivated to use information to positively impact their affect, reduce subjective sense of uncertainty and make decisions that lead to greater rewards (Bromberg-Martin & Sharot, 2020;Sharot & Sunstein, 2020).…”
Section: Introductionmentioning
confidence: 99%